Rh-Catalyzed Asymmetric Hydroformylation: The Case of Substituted and Heterocyclic Olefins - Tewari, Tanuja; Khopade, Kishor V.; Chikkali, Samir H. (ChemCatChem, 2025)
Asymmetric hydroformylation (AHF) of prochiral alkenes is an efficient way to synthesize optically active aldehydes, which are versatile chiral building blocks for pharmaceuticals, agrochemicals, and other fine chemicals. The purpose of this review is to take stock of developments in the last decade and shed light on the understanding of the field of AHF. So far, most of the literature methods focused on the use of Rh-based catalysts, due to high catalytic activity and excellent chemoselectivity for the aldehydes. Several chiral phosphorus ligands have been successfully developed for Rh-catalyzed AHF reactions. This review examines the role of the substrate/olefins in AHF. Several different types of ``mono-substituted'' terminal olefins (functionalized/nonfunctionalized) with a variety of chiral ligands have been investigated, which show high activity and excellent ee of up to 99%. The AHF of ``di-substituted'' and ``tri-substituted'' olefins is rarely reported. This review summarizes the evolution of chiral ligands for AHF. It discusses the progress made in desymmetrizing hydroformylation. In addition, it highlights important developments in AHF carried out with and without syngas. These advances span a wide variety of alkenes. Additionally, the review offers future approaches in the field of AHF for the synthesis of optically active aldehydes.
Keywords: Asymmetric hydroformylation; Asymmetric transfer hydroformylation; Chiral ligands; Desymmetrizing hydroformylation; Substituted alkenes

Ruthenium-catalyzed deconstruction of polyolefins: a strategy to up-cycle waste polyethylene to value-added alkene - Padhi, Ganeshdev; Khopade, Kishor V.; Moyilla, Nageswararao; Rangappa, Raghavendrakumar; Chikkali, Samir H.; Barsu, Nagaraju (Angewandte Chemie-International Edition, 2025)
Synthesis of value-added products from post-consumer waste polyolefins is fascinating as well as challenging. Here we report ruthenium-catalyzed up-cycling of the polyethylene to long-chain alkene derivatives. The developed methodology mainly involves two steps i.e., dehydrogenation of polyethylene through hydrogen atom transfer and its metathesis using the HG-II catalyst. The dehydrogenation of polyethylene using ruthenium catalysis derived up to 3.38 %, of double bonds; with 90 % of the recovered polyolefin material. The obtained unsaturated polyethylene was subjected to cross-metathesis with ethylene using HG-II catalytic system. This resulted in the synthesis of predominantly dodecene (C12) derivatives, with 58 % selectivity, along with other derivatives of varying chain lengths. The overall reaction produced terminal and internal olefins in the ratio 1:0.8 respectively. The dehydrogenation of polyethylene and its deconstruction was confirmed by NMR spectroscopy, Gel Permeation Chromatography (GPC) and Differential Scanning Calorimetry (DSC). The origin of C12 selectivity has been demonstrated by control experiments. The scope of the methodology was extended to post-consumer waste polyethylene which gave high conversion to value-added dodecene derivatives as a major product.
Keywords: Deconstruction; Homogeneous catalysis; ruthenium; Upcycling; Waste plastic